Reformed theological education and formation - Niemandt, Doret (Stellenbosch theological journal, 2023)
This article will hold up a mirror to the Reformed tradition's theological education past and present, specifically in the context of the DRC. This paper will also make proposals for the future, peering through the window towards possibilities for theological education and formation and the reformation of Reformed spirituality. The Reformed tradition has always maintained a high academic standard when it comes to theological education and the formation of its clergy. The curriculum used by the DRC, modelled on the European system, still to a great extent reflects the needs of the church decades ago and is challenged by the DRC's current ecclesiological understanding. A missional church, as portrayed by the DRC's policy document, requires missional clergy, or missional leadership, and thus theological education that supports this type of formation. This article proposes a more holistic spiritual formation programme that cultivates a sound Reformed spirituality and enables the formation of these missional leaders.